2010
DOI: 10.1038/onc.2010.146
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pyrimidine nucleotide carrier (PNC1) regulates mitochondrial biogenesis and the invasive phenotype of cancer cells

Abstract: The insulin-like growth factor (IGF-I) signalling pathway is essential for metabolism, cell growth and survival. It induces expression of the mitochondrial pyrimidine nucleotide carrier 1 (PNC1) in transformed cells, but the consequences of this for cell phenotype are unknown. Here we show that PNC1 is necessary to maintain mitochondrial function by controlling mitochondrial DNA replication and the ratio of transcription of mitochondrial genes relative to nuclear genes. PNC1 suppression causes reduced oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 47 publications
3
67
0
Order By: Relevance
“…Slc25a33-mediated uptake of UTP is important for transcription and replication of mitochondrial DNA, which again is important for mitochondrial function, i.e. increased expression of Slc25a33 enables a cancer cell to optimally produce ATP and grow while it also protects the cell from metabolic stress by preventing increased production of reactive oxygen species (Favre et al 2010). This is therefore another effect of insulin and X10 that provides cancer cells with a growth advantage.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Slc25a33-mediated uptake of UTP is important for transcription and replication of mitochondrial DNA, which again is important for mitochondrial function, i.e. increased expression of Slc25a33 enables a cancer cell to optimally produce ATP and grow while it also protects the cell from metabolic stress by preventing increased production of reactive oxygen species (Favre et al 2010). This is therefore another effect of insulin and X10 that provides cancer cells with a growth advantage.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…The category transport contained several members of the solute carrier gene family, including SLC2A1 (glucose transporter), SLC7A3 (cationic amino acid transporter), SLC12A2 (sodium, potassium, and chloride transporter), SLC25A5 (mitochondrial carrier, adenine nucleotide translocator), SLC25A33 (mitochondrial carrier), SLC39A2 (zinc transporter), and SLC40A1 (iron transmembrane transporter). The two mitochondrial transporters, SLC25A5 and SLC25A33, have a role in cellular energy metabolism [68] and mitochondrial maintenance [69]. For the expression of the glucose transporter gene SLC2A1, regulation by conceptus prostaglandins has been shown recently in the ovine uterus [70], indicating that additional conceptus-derived factors influence the endometrial gene expression.…”
Section: Genes Not Regulated After Ifna2 Administration But On D15 Anmentioning
confidence: 99%
“…Additionally, we have recently shown that miR-200c, an miRNA only modestly expressed in the heart, is increased in ZO rat heart, and this increase in miR-200c may serve as a compensatory mechanism to downregulate excessive activation of the nutrient sensor kinase S6K1 [176] . The miR-200 family is implicated in the epithelial-to-mesenchymal transition (EMT) that is accompanied by mitochondrial biogenesis and involved in organ fibrosis and carcinoma progression [177][178][179][180][181][182][183][184] . It was reported that miR-200 is down-regulated in EMT, and that overexpression of miR-200b can attenuate EMT [179] .…”
Section: Mirna Regulation Of Apoptosismentioning
confidence: 99%